Governança cooperativa: um estudo de caso sobre as mudanças após a padronização das práticas pelo Banco Central do Brasil - Jansen, Aline Castro (2017)
The concern surronding the development of the governance has progressed every day, bearing in ming the constant search for a more effective management in the most varied organizations, therefore, the cooperatives are being included in this niche. Based on this, and seeking to improve the supervision of credit cooperatives, Brazil’s Central Bank (BACEN) conducted a survey between 2006 and 2009, where the concept of cooperative governance was defined. On that account, the present study has analyzed how the application of cooperative governance mechanisms occurs in cooperatives of free credit admission after the standardization of governance practices by Brazil’s Central Bank, from the perspective of the institutional theory. To achieve this goal, the qualitative approach was used among the strategy of case study in a cooperative of free credit admission in the city of Pelotas / RS. That way, seven semi-structured interviews were used, using the snowball technique and the saturation sampling. In addition, in loco observations and documentary research were also carried out in the unit of analysis. The results showed that one of the main changes after the disclosure of good governance practices by BACEN (2009) was regarding the definition of the roles, which is exclusively strategic for the Board of Directors and only operational for the Executive Board. Another relevant modification perceived in this research was the use of the Centre Coordinators as representatives of their own groups in the General Assembly voting, taking the vote of what was decided previously in the Centre Assemblies, in which an increase among the members was founded in the participation rates. In summary, the downside of this study was that the research was done with some employees within the cooperative, not adding the opinion of others stakeholders. Consequently, it is suggested as a future study to investigate the members' perception on the governance structures used by the cooperatives. Finally, this work resulted in theoretical and managerial contributions to support the cooperative governance theme.